Macrophages treated with particulate matter PM2.5 induce selective neurotoxicity through glutaminase‐mediated glutamate generation. (19th May 2015) - Liu, Fang; Huang, Yunlong; Zhang, Fang; Chen, Qiang; Wu, Beiqing; Rui, Wei; Zheng, Jialin C.; Ding, Wenjun
Abstract Exposure to atmospheric particulate matter PM2.5 (aerodynamic diameter ≤ 2.5 μm) has been epidemiologically associated with respiratory illnesses. However, recent data have suggested that PM2.5 is able to infiltrate into circulation and elicit a systemic inflammatory response. Potential adverse effects of air pollutants to the central nervous system (CNS) have raised concerns, but whether PM2.5 causes neurotoxicity remains unclear. In this study, we have demonstrated that PM2.5 impairs the tight junction of endothelial cells and increases permeability and monocyte transmigration across endothelial monolayer in vitro, indicating that PM2.5 is able to disrupt blood–brain barrier integrity and gain access to the CNS. Exposure of primary neuronal cultures to PM2.5 resulted in decrease in cell viability and loss of neuronal antigens. Furthermore, supernatants collected from PM2.5‐treated macrophages and microglia were also neurotoxic. These macrophages and microglia significantly increased extracellular levels of glutamate following PM2.5 exposure, which were negatively correlated with neuronal viability. Pre‐treatment with NMDA receptor antagonist MK801 alleviated neuron loss, suggesting that PM2.5 neurotoxicity is mediated by glutamate. To determine the potential source of excess glutamate production, we investigated glutaminase, the main enzyme for glutamate generation. Glutaminase was reduced in PM2.5‐treated macrophages and increased in extracellular vesicles, suggesting that PM2.5 induces glutaminase release through extracellular vesicles. In conclusion, these findings indicate PM2.5 as a potential neurotoxic factor, crucial to understanding the effects of air pollution on the CNS. We propose the following cascade of events for PM2.5‐induced neurotoxicity: PM2.5 is inhalable and able to infiltrate into circulation. Circulating PM2.5 impairs tight junction of endothelial cells, disrupts blood–brain barrier integrity, and gains access to the central nervous system. PM2.5 induces neuronal injury directly or through macrophages and microglia by the elevated production of glutamate. The discovery of this cascade of events supports an adverse effect of air pollution on the central nervous system.